Domain science and engineering from computer science to the sciences of informatics. Part I: Engineering - Bjorner, D. (Кибернетика и системный анализ, 2010)
Висловлено побажання, щоб факультети комп’ютерих наук викладали програмування і програмну інженерію на основі формальних методів і більше уваги приділяли дослідженню формальних методів для надійної розробки програмного забезпечення, а також щоб поняття науки і інженерії проблемної області стали незамінною частиною науки інформатики і програмної інженерії. In this paper we wish to advocate that departments of computer science put emphasis on teaching programming and software engineering based on formal methods; and more emphasis on research into formal methods for the trustworthy development of software. We also wish to advocate that the concepts of domain science and domain engineering become an indispensable part of the science of informatics and of software engineering.